The Outcome of Treatment with Recombinant Tissue Plasminogen Activator in Acute Ischemic Stroke - Alia Saberi; Amirreza Ghayegran; Mojtaba Abbasalizade; Zeinab Ehtiatkar; Samaneh Ghorbani Shirkouhi; Parisa Shahshahani; Hamidreza Hatamian; Sasan Andalib (Caspian Journal of Neurological Sciences, 2021)
Background: Thrombolytic therapy is the recommended treatment of acute ischemic stroke. It is crucial to evaluate the treatment results with recombinant Tissue Plasminogen Activator (r-TPA) in patients with acute stroke. Objectives: This study aimed to evaluate treatment outcomes with r-TPA in patients with acute stroke in a referral stroke center in Iran. Materials & Methods: In this retrospective study, 87 patients with symptoms of acute stroke were examined. They were referred to a stroke center in Gilan Province, Iran, from June 2016 to April 2020 and received r-TPA (0.9 mg/kg). Demographic information, the time interval between the onset of symptoms and r-TPA administration, complications, and National Institutes of Health Stroke Scale (NIHSS) upon arrival and discharge and death of patients were extracted from their hospital files. The paired t-test, independent t-test, and Pearson correlation test were used to compare variables using IBM SPSS for Windows version 20.0 (IBM Corp., Armonk, NY, USA). Results: The Mean±SD of NIHSS reduced from 14.7±6.4 to 8.9±7.6 (P<0.001). The most common complication was Intracerebral Hemorrhage (ICH) (12.6%). The hospital mortality rate was 23%. ICH occurred among 40% (n=8) of those who expired, and 4.47% (n=3) of them survived, and this difference was significant (P<0.001). Conclusion: The recovery with r-TPA administration in the stroke center was acceptable. Mortality and ICH occurrence rates were higher than other non-Iranian studies. It seems that we should change the case selection criteria and prescription dose to achieve better results of treatment with TPA.